Evaluasi Tata Kelola TI pada Sistem Informasi Akademik Menggunakan Cobit 5 (Studi Kasus Sistem Informasi Akademik di STT Terpadu Nurul Fikri) - Ahmad Algifari; Nugroho Dwi Saputra; Misna Asqia (DBESTI: Journal of Digital Business and Technology Innovation, 2026)
Sekolah Tinggi Teknologi Terpadu Nurul Fikri is a higher education institution that utilizes the Academic Information System (SISKA) to support the efficiency of academic services. Although the system has been implemented, various obstacles are still encountered, including low user understanding, an unfriendly interface, and a lack of socialization. This study aims to evaluate the maturity level of IT governance in SISKA using the COBIT 5 framework, with a focus on the DSS02 domain (Manage Service Requests and Incidents). The research method uses an evaluative mixed-methods approach, involving the distribution of questionnaires to 164 active students and interviews with system administrators. The instruments were developed based on the seven subprocesses within DSS02 and tested for validity and reliability. The results indicate that SISKA is at capability level 3 (Established Process), while the expected level is 4 (Predictable Process), resulting in a GAP of 1. These findings suggest that governance processes are consistent and well-documented, but still require strengthening in monitoring, reporting, data-based evaluation, and improving the quality of system socialization to users.